Bosworth fracture. An atypical case of irreducible ankle fracture-dislocation. (August 2020) - Martin-Somoza, Francisco Jose; Picazo, David Ruiz; Cabezuelo, Jesús Amador Martinez; González, Ana Verdejo
Abstract: An irreducible ankle-fracture dislocation in which the proximal fibular shaft fragment locks behind the posterior tibial tubercle is defined as "The Bosworth injury". Characteristically, this fracture is generally not reducible using closed methods. A high number of attempts can be counterproductive to get a good final functional result and it may also lead to the appearance of future complications. Although it is a recognized and published cause of irreducible ankle dislocation, it is an unusual and rare injury. The initial radiological diagnosis is difficult, usually going unnoticed, and it is frequently diagnosed during the surgical act, appreciating the retrotibial position of the proximal fibular fragment. The present report is the first in the medical data to describe a case of Bosworth injury in a 32-week-old pregnant woman. The initial diagnosis went unnoticed. After unsuccessful closed reduction attempt, urgent surgical intervention was performed. Highlights: An irreducible ankle-fracture dislocation in which the proximal fibular shaft fragment locks behind the posterior tibial tubercle is defined as "The Bosworth injury" Although it is a recognized and published cause of irreducible ankle dislocation, it is an unusual and rare injury. The initial radiological diagnosis is difficult, usually going unnoticed, and it is frequently diagnosed during the surgical act. An open reduction and internal fixation is needed.